AN ANALYSIS OF TRANSLATING PROCEDURES ON SONY ERICSSON LIVE WITH WALKMAN SERIES STARTUP GUIDE - Naufal Purnama Satriadi (Journal of English and Education, 2014)
The present research entitled Analysis of Translating Procedures on Sony Ericsson Live with Walkman Series Startup Guide aims at analyzing the translation procedures and determining the translation quality of Sony Ericsson Live with Walkman Startup Guide. A qualitative descriptive method was employed to analyze the data by referring to two theories of translating procedures proposed by Newmark (1988) and Vinay Darbelnet (2000) and a number of theories of quality of translation: Barnwell (1980, in Larson 1984), Larson (1984), etc. The result of data analysis shows that there are six translation procedures found in the text: Borrowing or Transference (54 items or 27%), Calque or Through Translation (12 items or 6%), Literal or Word for Word Translation (31 items or 15.5%), Transposition (42 items or 21%), Adaptation or Naturalization (43 items or 21.5%), and Reduction (18 items or 9%). Moreover, the data analysis result also reveals that the quality of translation is good based on the percentages of acceptable translation (94%) and unacceptable translation (6%). In the words level there are 76 acceptable items and 10 unacceptable items. Next, in the phrases level there are 60 acceptable items and 2 unacceptable items. Then, in the sentences level there are 52 acceptable items and no unacceptable items. Furthermore, the total acceptable items in the text are 188 items (76 words, 60 phrases, and 52 sentences) or 94 % from 200 items and for the unacceptable items there are 12 items (10 words, 2 phrases, and 0 sentences) or 6% from 200 items. Keywords: Translation procedures, Translation quality